Parental Responsibility Of Children Crime In Indonesian Criminal Adat Law - Fardiansyah, Ahmad Irzal; Suseno, Sigid; Rukmini, Mien; Sulistiani, Lies (Jurnal Hukum & Pembangunan, 2020)
Children who are in conflict with the law cannot be separated from the responsibilities of parents as the first party in the childs environment. The relationship between parents and children is a harmonized relationship from a strong emotional connection on the basis of blood relations. This situation makes parents unable to release and be released responsibility for their childrens behavior. When children are faced with the law, policies to take over the responsibility of supervising children from parents, by denying that parents actually have the opportunity to deal with the problems of children who are dealing with the law are more often chosen. Even though the responsibility is transferred from the parents, they will find it difficult to rebuild the relationships they previously had with their children. This connection shows that parents also play a role when their children commit criminal acts indirectly.